2022
DOI: 10.3389/fcvm.2021.799605
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Scoring Model for Postoperative Tracheostomy in Patients Who Underwent Cardiac Surgery

Abstract: BackgroundA subset of patients require a tracheostomy as respiratory support in a severe state after cardiac surgery. There are limited data to assess the predictors for requiring postoperative tracheostomy (POT) in cardiac surgical patients.MethodsThe records of adult patients who underwent cardiac surgery from 2016 to 2019 at our institution were reviewed. Univariable analysis was used to assess the possible risk factors for POT. Then multivariable logistic regression analysis was performed to identify indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Undergoing a tracheostomy is an important indicator of the increased risk of poor prognoses in patients undergoing cardiovascular surgeries [ 3 , 7 , 9 , 20 ], which was again confirmed in the current study. Due to the difference of surgical populations in different studies, the reported rates of POTs in the previous literature were quite different [ 3 , 7 , 8 , 9 , 10 , 11 ]. The overall incidence rate of POTs after HVS was 1.8% in our analysis, falling within the range of incidence rates reported in the previous literature [ 3 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Undergoing a tracheostomy is an important indicator of the increased risk of poor prognoses in patients undergoing cardiovascular surgeries [ 3 , 7 , 9 , 20 ], which was again confirmed in the current study. Due to the difference of surgical populations in different studies, the reported rates of POTs in the previous literature were quite different [ 3 , 7 , 8 , 9 , 10 , 11 ]. The overall incidence rate of POTs after HVS was 1.8% in our analysis, falling within the range of incidence rates reported in the previous literature [ 3 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
“…Being of an older age was identified to associate with a higher risk of POTs in the current study; however, the results of whether the risk of POTs would increase with age were inconsistent in previous studies, which may be due to the difference in disease types and study populations [ 4 , 22 , 23 ]. Diabetes mellitus and pulmonary edema as risk factors for POTs have also been reported in previous studies, which may be mainly associated with higher risks of various pulmonary complications [ 7 , 24 , 25 ]. The relationship between combined aortic surgery and ventilation dependence was reported a long time ago, and patients undergoing aortic procedures have been identified to have a higher risk of respiratory failure [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Weiss and Rady et al reported that emergency surgery correlated significantly with time to extubation and lung injury, and was independent predictor of early postoperative pulmonary dysfunction ( 27 , 28 ). Previous studies have identified the close relationship between renal insufficiency and various postoperative complications after cardiovascular surgery, such as hypoxemia, pneumonia, hyperlactatemia, and tracheostomy ( 3 , 29 33 ). Although the related researches on the relationship between renal insufficiency and hypoxemia are limited and the exact mechanisms remain to be further investigated, we guess that inflammatory responses, erythropoietin production by the kidney, and the subsequent oxygen delivery may be involved ( 34 ).…”
Section: Discussionmentioning
confidence: 99%